Risk Analysis of Optimization of FDI in Indonesia Evidence of Cointegration Modeling and ECM - Joshua Perkasa Naibaho; Magit Les Denny Tewu; Martua E. Tambunan (Indonesian Journal of Multidisciplinary Science, 2022)
Foreign Direct Investment (FDI) is one of the superior strategies commonly used by governments from developing countries to obtain funding for development. Because of the research that concentrates on risk management, the authors tried to use six free variables derived from the economic framework.  The goal is to be able to find out how the selected free variables affect long - term and short - term FDI optimization.  Then from the six variables, the author identified unexpected incident which can cause the risk of FDI optimization in Indonesia. Error correction model is the method used by the author to process the data. The results showed similar results for both the long and short term. Exports and foreign debt are variables that do not significantly affect the presence of FDI in Indonesia. Meanwhile, interest rates and exchange rates are free variables that have a positive and significant effect, while labor and GDP have a negative and significant effect.